Concepts of innovation for and from emerging markets - Martin Albert (Technische Universität Chemnitz, Professur für Innovationsforschung und Technologiemanagement, 2016)
A closer look at innovation for and from emerging markets respectively developing economies reveals that a variety of different terms and concepts related to this type of innovation exist. The goal of my conceptual paper is to present a comprehensive overview of related terms and concepts and to suggest theoretical based classification criteria in order to differentiate them. After a first investigation in relation to innovation for and from emerging markets the keywords "reverse", "frugal", "jugaad", and "bottom of the pyramid / bottom of pyramid / bop" were identified and used for searching the database of Google Scholar. For further investigation only texts were considered with at least eight various terms. 19 different texts were identified which classified for a further analysis. As results 33 identified terms in relation to innovation for and from emerging markets, various spellings and synonyms and references with at least two mentions in the identified texts are presented. As theoretical based classification criteria "market orientation", "determinants" (of innovation for and from emerging market)", "natur" (of innovation for and from emerging markets), "sophistication", "sustainability", "novelty" and "innovator type" were identified.
Keywords: 650; innovation; emerging markets; developing economies; classification criteria; frugal; innovation; bottom of the pyramid; reverse innovation; jugaad